2022
DOI: 10.3390/ijerph19116607
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Frequent Emergency Department Use and Hospitalization among Patients with Substance-Related Disorders Recruited in Addiction Treatment Centers

Abstract: Few studies have assessed the overall impact of outpatient service use on acute care use, comparing patients with different types of substance-related disorders (SRD) and multimorbidity. This study aimed to identify sociodemographic and clinical characteristics and outpatient service use that predicted both frequent ED use (3+ visits/year) and hospitalization among patients with SRD. Data emanated from 14 Quebec (Canada) addiction treatment centers. Quebec administrative health databases were analyzed for a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…In line with previous studies, there was an association between alcohol and other drug use disorders and an enhanced risk for ED use and hospitalization among patients with SRDs (Armoon et al, 2021; Fleury et al, 2022). The studies highlighted that the main abused substances among patients with SRDs included alcohol (Wu et al, 2012) and cannabis (Campbell et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…In line with previous studies, there was an association between alcohol and other drug use disorders and an enhanced risk for ED use and hospitalization among patients with SRDs (Armoon et al, 2021; Fleury et al, 2022). The studies highlighted that the main abused substances among patients with SRDs included alcohol (Wu et al, 2012) and cannabis (Campbell et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Two other variables that have been shown to predict readmission are having a previous history of treatment and being referred to addiction treatment by medical services. Regarding the former variable, our study has shown that this is associated with the time spent in treatment (patients with previous admissions spend less time in treatment), and other studies have shown its relationship with treatment outcomes [57, 58]. Regarding the latter variable, the observation that readmission is less common among those who have been referred by a clinician could reflect the fact that healthcare professionals have greater authority or influence than others in promoting the benefits of starting addiction treatment.…”
Section: Discussionmentioning
confidence: 56%
“…High ED use referred to a minimum of 3+ ED visits per year. 32,33 Studies report that high ED users are often patients without adequate follow-up care, 34 and that ED care is one of the costliest options. 35…”
Section: Methodsmentioning
confidence: 99%